Kinerja Peralatan Bongkar General Cargo (Steel Coil) Pada MV.Grace Zephyr Oleh PT Daisy Mutiara Samudra Tanjung Priok - Muhammad Aris Rafli; Siti Sahara (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The development of loading and unloading technology requires ports to increase their role and function as terminal points for goods and ships. Of course, appropriate loading and unloading equipment is needed, both mechanical and non-mechanical equipment. problems faced in the loading and unloading process on the MV Grace Zephyr. Namely: the influence of the performance of loading and unloading equipment on the smoothness of the loading and unloading process and the efforts that need to be made to optimize the use of loading and unloading equipment. In accordance with the problems faced in optimizing equipment performance, temporary answers to the problems raised have emerged, including the suspicion that the reason the loading and unloading process can take a long time is due to the need to be careful in installing the sling belt and the lack of maintenance of the loading and unloading equipment, which hinders the loading and unloading process.